The Influence of Compensation and Work Discipline on Employee Performance PT. Matahari Department Store Karawang - Ais, Ropahal; Solehudin , Solehudin; Nurhasanah , Nunung (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Low staff performance will hinder organizational goals. Management must consider salary and work discipline while producing human resources to fulfill company goals and increase performance. This study examines the relationship between compensation and work discipline and their partial and simultaneous effects on employee performance at PT Matahari Department Store Karawang branch. This study uses descriptive and verification methodologies. Sample Random Sampling was used to acquire 104 samples from 140 persons. Data analysis is done using scale range analysis and path analysis using MSI, Excel 2010, and SPSS version 23. This research found that PT Matahari Department Store Karawang employees' compensation averages 402, which is on the agreed scale range, and that their work discipline averages 401, which is on the agreed scale. The correlation analysis score of 0.456 shows a substantial association between remuneration and work discipline. Performance is partially influenced by remuneration (27.8%) and work discipline (19%). The study found a 46.8% correlation between salary and work discipline and employee performance at PT Matahari Department Store Karawang. The remaining 53.2% was due to other variables (?) not addressed in this study